Enhanced value stream mapping for streamlining supply chains in the furniture manufacturing industry - Muhammad Ariff Fauzan, Mat Rodzi; Nik Mohd Zuki, Nik Mohamed; Fazilah, Abdul Aziz (Penerbit UMP, 2025)
This study aims to analyze and optimize the supply chain processes of a furniture fabrication company by leveraging Value Stream Mapping (VSM) and simulation software. The current production system is meticulously modeled to identify inefficiencies and bottlenecks, enabling targeted improvements. Using Tecnomatix, both Current State and Future State Mappings are developed to enhance operational efficiency, minimize waste, and streamline workflows. The study commences with comprehensive data collection, followed by a detailed analysis of the Current State Mapping, revealing key inefficiencies such as excessive movement, prolonged waiting periods, and a lack of standardized work procedures. Based on these findings, a Future State Mapping is designed to optimize production flow. Among the alternatives evaluated, Scenario 2 emerges as the most effective, incorporating Kaizen principles in the measurement and cutting process across three workstations. This scenario achieves the highest output of seven units per shift, outperforming other scenarios while maintaining five operators and reducing the number of workstations from 13 to 10. Additionally, Scenario 2 exhibits the lowest lead time, ensuring a seamless production flow with minimized idle time. Scenario 1 effectively reduced waiting time by merging workstations, while Scenario 2, incorporating Kaizen, led to a 40% increase in output while maintaining the same workforce Although waiting and total processing times show slight increases, they remain within acceptable working limits. By implementing these strategic improvements, this study successfully reduces waste, enhances productivity, and promotes sustainable manufacturing practices, ultimately benefiting the industry and the broader economy.